Capitalism and nature in South Africa: racial dispossession, liberation ideology and ecological crisis - Andrews, Donna (Department of Political Studies, 2018)
This dissertation is an historical examination of policy and discourse as it impacts on ecological questions in South Africa, with a focus on land, mining and fishing. It shows how ecological issues are embedded in relations of class, race and gender. It argues that relation of nature and society and social relations form each other historically. Specifically, it makes visible how apparently progressive ideas to overcome the legacy of apartheid have served to perpetuate the ecological crisis after the end of apartheid. That is, although liberation ideology aims to overcome irrational and harmful forms of domination, current strategies of overcoming racial dispossession on the basis of capitalism rely on increasing and unbridled exploitation of natural resources. The dissertation concludes with a consideration of political perspectives and agency responding to the ecological crisis in South Africa today. It provides a survey of government, activist and community initiatives and assesses their capacity to help create a new relationship of nature and society, as the basis for a new society.